Clinical case of meningoencephalitis of Epstein-Barr viral etiology in an immunocompetent patient - O.O. Popovych; L.V. Moroz; F.A. Chabanov; O.S. Androsova; S.M. Kulias; K.D. Chichirelo-Konstantynovych; L.P. Plotytsia (Medičnì Perspektivi)
The article describes a rare clinical case of meningoencephalitis of Epstein-Barr viral (EBV) etiology in an immunocompetent patient. The purpose of the work was to acquaint practitioners with the problems of diagnosis and treatment of EBV-neuroinfection, features of the course and management of EBV-meningoencephalitis. The woman, 46 years old, was admitted to the intensive care unit with a diagnosis of mushroom poisoning. Based on clinical-laboratory-instrumental examinations the diagnosis of EBV-meningoencephalitis was made. EBV DNA was detected in the cerebrospinal fluid by polymerase chain reaction (PCR) and magnetic resonance imaging (MRI) of the brain showed focal changes in the left temporal-insular region with signs of leptomeningitis. Taking into account the specifics of this case, the authors of the article came to the following conclusions: EBV-meningoencephalitis can occur in people with normal immune status under conditions of psychological and physical stress; delayed diagnosis of meningoencephalitis at the onset of the disease in this case is associated with the prevalence of clinical manifestations of general brain syndrome, mistakenly regarded as symptoms of intoxication and dyspepsia due to food poisoning; meningoencephalitis of EBV-etiology is accompanied by signs of convulsive, atactic, cognitive and mental syndromes; temporal-insular localization of focal brain changes may be characteristic for EBV-meningoencephalitis; treatment with acyclovir and glucocorticoids may have benefits; complicated vascular anamnesis, bed rest and glucocorticoid therapy predict an increased risk of venous thrombosis, which in this patient was realized as acute sural phlebothrombosis; according to MRI the resolution of leptomeningitis and focal brain changes with gliosis formation occurred 3 months after manifestation of the disease; the risk of the following neurological pathologies due to specific localization of gliosis should be considered and requires medical control.